Differential Pulse Code Modulation of colour television signals using various prediction methods - Hamid Gharavi (1980)
Predictive coding, which is often associated with differential pulse code modulation (DPCM), can offer an attractive means of data compression of television signals. This thesis describes investigations of various adaptive and non-adaptive DPCM schemes in order to reduce the high bit-rate required for the transmission of broadcast quality colour television signals. [Continues.]